Histories and philosophies of carceral education: aims, contradictions, promises and problems - Harmes, Marcus K.; Harmes, Barbara (Springer eBook Collection, 2022)
This edited collection encourages philosophical exploration of the nature, aims, contradictions, promises and problems of the practice of education within prisons around the world. Such exploration is particularly necessary given the complex operational barriers to education, and higher education in particular, within prison-based teaching and learning. These operational barriers are matched by cultural and polemical barriers, such as the criticism of diverting resources to and spending money on prisoner education when the cost of some education seems prohibitive for people outside prison. More so than in other education contexts, prison education may fall short of higher ideals because it is shot through with both practical and moral-political problems and challenges, especially in the age of global late capitalism, high technology and mass incarceration or securitization. This book includes insights and issues around a wide range of areas including: ethics, religion, sociology, justice, identity and political and moral philosophy. Marcus K Harmes is Professor at the University of Southern Queensland, Australia. He has published extensively in the fields of religious and political history, with a particular emphasis on British religious history and popular culture. He is the author of numerous studies on the church in modern popular culture, especially on film and television, including book chapters in the collections Doctor Who and Race and Time and Relative Dimensions in Faith. Barbara Harmes lectures at the University of Southern Queensland, Australia. Her doctoral research focussed on the discursive controls built around sexuality in late-nineteenth-century England. Her research interests include cultural studies and religion. She has published in areas including modern Australian politics, 1960s American television and her original field of Victorian literature. Meredith Harmes teaches communication and also works in the enabling programs at the University of Southern Queensland in Australia. Her research interests include modern British and Australian politics and popular culture in Britain and America.